High expression of Oct4 and Nanog predict poor prognosis in intrahepatic cholangiocarcinoma patients after curative resection - Zhang, Mei-xia (J Cancer, 2019)
Oct4 and Nanog are reported to promote tumor progression in several cancers, but the effect on intrahepatic cholangiocarcinoma (ICC) is unknown. The aim of our present study was to explore the prognostic role of Oct4 and Nanog on patients with ICC. Immunohistochemistry was used to detect the expression of Oct4 and Nanog in a random cohort of 116 ICC patients, and validated in another independent cohort of 103 patients. Prognostic nomograms were formulated for OS and RFS prediction of ICC patients. Our results showed Oct4 and Nanog highly expressed in ICC tumor tissues and were identified as independent prognostic factors for patients' OS and RFS. Significant positive correlation was found between Oct4 and Nanog expression. Co-expression of Oct4 and Nanog implied the poorest OS and RFS in ICC patients. Our nomograms comprising Oct4 and Nanog achieved better predictive accuracy in training and validation cohorts compared with AJCC 7th edition and LCSGJ stage for OS and RFS prediction. Our study support the high expression of Oct4 and Nanog in ICC implies aggressive tumor behaviors and suggest a poor clinical prognosis, which emerges as valuable biomarkers for identifying patients at high risk after curative resection.